Peran Asistensi Mengajar Angkatan Empat dalam Meningkatkan Motivasi Belajar Siswa Kelas VIII pada Mata Pelajaran IPS di SMP Negeri 3 Maumere - Winda Winda; Rimasi Rimasi (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This research aims to determine the role of teaching assistance in the fourth generation campus teaching program in increasing student learning motivation, especially for seventh grade students in social studies subjects at SMP Negeri 3 Maumere. Teaching assistance is one part of the Teaching Campus program of the Merdeka Belajar Kampus Merdeka (MBKM) activities. This activity aims to empower students to help with the learning process in elementary and middle schools in various villages/cities, one of which is at SMP Negeri 3 Maumere which is in Sikka Regency, East Nusa Tenggara Province. In this program, students are responsible for assisting the school in the teaching process, assisting with technology adaptation, and assisting with administration. Apart from that, students have a responsibility to improve students' morals and increase students' learning motivation and interest in learning while at school. The results of this research show that the role of teaching assistance plays a very important role in maintaining and growing students' learning motivation, especially in seventh grade students at SMP Negeri 3 Maumere. The results of this program are expected to be able to foster social sensitivity in students to hone their thinking skills. work together with teachers and students across fields of science to solve the problems they face.